Pengaruh Manajemen Karir, Worklife Balance Terhadap Retensi Karyawan dengan Moderasi Kepemimpinan (Studi pada Pilot PT Garuda Indonesia) - Rhizky Dirga Pratama; Yuni Kasmawati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Employee retention is one of the biggest challenges faced by companies in today's increasingly competitive workplace, especially in the aviation sector, which is characterized by high training costs, demands for maintaining flight safety, and disruptions to flight operations. Therefore, companies need to retain their pilots so they didn't move to other companies. This study aims to analyze the influence of career management and work-life balance on employee retention, moderated by leadership at PT Garuda Indonesia. This study uses a quantitative approach with a causal approach. The population of this study consisted of all 483 B 737 pilots at PT Garuda Indonesia, using a probability sampling technique. Data were collected through questionnaires distributed to randomly selected respondents. Data analysis was carried out using SEM (Structural Equation Model) with the PLS (Partial Least Square) approach to test the relationship between existing variables. Data analysis in this study includes the outer model, inner model, and hypothesis testing. The results showed that career management has a positive and significant effect on employee retention. Work-life balance has a positive and significant effect on employee retention. Leadership does not moderate the effect of career management on employee retention. Similarly, leadership does not moderate the effect of work-life balance on employee retention.